Interaction studies on lumpfish exposed to Atlantic salmon : behavioural observations and the underlying physiological and neurobiological mechanisms - Staven, Fredrik Ribsskog (Nord University, 2022)
Doctoral thesis (PhD) – Nord University, 2022 publishedVersion